Pengeluaran Lochea Rubra Ditinjau dari Mobilisasi Dini Pada Ibu Pasca Operasi Sectio Caesarea - Astriana, Willy (Universitas Aisyah Pringsewu, 2016)
Sectio Caesarea is labor through incisions the abdominal wall. Patients Sectio caesarea post-surgical in the first 6 hours is recommended to immediately move the arm, hands, feet and toes to make the work the digestive organs can be return to normal. This study aims to determine the correlation of early mobilization of maternal post-operative sectio caesarea with emanation of lochea rubra. The method used is cross sectional analytical survey and sampling technique uses accidental sampling method using a check list sheets as an instrument. The population in this study are all women who have recently undergone surgery sectio caesarea. Chi-square test results obtained p value 0,001 less than 0,05.Keywords : early mobilization, lochea rubra, Sectio Caesarea